New antenna for milimetre wave radar - Muhammad Nazrol, Zawawi (2015)
This project has been conducted in Laboratoire d'Electronique, Antennes et Télécommunications (LEAT) in Sophia Antipolis and is funded by Universiti Malaysia Pahang (UMP) under the doctorate grant awarded by the Ministry of Education Malaysia (MOE). The supervisor for this project is Claire Migliaccio (Professor at University Nice Sophia Antipolis) and assisted by Jerome Lanteri (Associate professor at University Nice Sophia Antipolis).